The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1939
DOI: 10.4039/ent71243-11
|View full text |Cite
|
Sign up to set email alerts
|

Time of Cut as a Factor Influencing Infestation of Coniferous Logs

Abstract: During the summer months, dead and weakened trees and logs left in the woods are subject to attack by a variety of insects, mainly of the order Coleoptera. Some are wood-boring forms which cause a depreciation in the potential value of the lumber; others are barkbeetles which at times may build up in numbers sufficient to cause a primary attack on the living stand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1957
1957
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 1 publication
(1 reference statement)
0
4
0
Order By: Relevance
“…The most numerous of all species of cerambycids found in the fire-killed trees, this species has been reported breeding in pine, spruce, and balsam fir (Morley, 1939). Large numbers were found in all three pines that had been killed by the fire.…”
Section: Acmaeops Proteus Kbymentioning
confidence: 87%
“…The most numerous of all species of cerambycids found in the fire-killed trees, this species has been reported breeding in pine, spruce, and balsam fir (Morley, 1939). Large numbers were found in all three pines that had been killed by the fire.…”
Section: Acmaeops Proteus Kbymentioning
confidence: 87%
“…Damaging organisms such as insect pests can be present in harvest debris (e.g. Morley, 1939;Hayes et al, 2008) and may serve as a catalyst for outbreaks in surrounding stands or damage to nearby logs and other forest products. Bark beetles, such as the pine engraver (Ips pini Say), that can cause mortality in conifers, commonly colonize and reproduce in harvest debris (Hayes et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…However, early work in Canada indicated that several Monochamus spp. successfully attacked logs that had been left in the forest from September of the previous year, indicating that bark retains its attractiveness over winter (Morley, 1939). In Europe, studies by Tragardh (1939) on trees that had been damaged in a wind storm on 1 May were not attacked by M .…”
Section: Monochamus Sppmentioning
confidence: 96%
“…Throughout North America, Monochanzus spp. have a long history as secondary pests causing degradation of timber through the boring activities of the larvae and the introduction of blue-staining fungi (Morley, 1939;Raske, 1973;Gardiner, 1975). Any coniferous forest has a high probability of a resident population of Monochamus spp.…”
Section: Entry To Pathwaymentioning
confidence: 99%